Pengaruh harga diri terhadap kesejahteraan psikologis dan kesepian pada Mahasiswa - M. Salis Yuniardi; Hayundaka, Anandam Hayundaka (Psychological Journal: Science and Practice, 2023)
International students studying abroad face various challenges such as having to adapt to different socio-culturalconditions. This can affect psychological well-being, which can hinder the academic process. Factors that are thought toaffect psychological well-being are self-esteem and loneliness. The subjects in this study were 122 Indonesian studentsfrom various levels of education who were studying abroad. The scales used were Rosenberg Self-Esteem Scale,Ryff Psychological Well-Being Scale, and UCLA Loneliness Scale. Analysis in this study uses PROCESS Hayes 4.0mediation. Results showed loneliness mediated the relationship of the effect of self-esteem on psychological well-being.This shows that the important influence of self-esteem on psychological well-being occurs directly or indirectly mediatedby loneliness. The higher the self-esteem, the lower the loneliness, and then the better the psychological well-being.